Vestibular substitution: Comparative study - (:unkn) unknown (My University, 2010)
Objective: To determine the efficacy of vestibular rehabilitation with the electrotactile vestibular substitution system, as a new treatment modality in patients with bilateral vestibular disorders.Study design and settings: Nineteen patients with bilateral, chronic, idiopathic vestibulopathy were studied prospectively. Patients were divided to two groups. Patients in the first group were rehabilitated with the electrotactile vestibular substitution system, while patients in the second group were treated with standard vestibular rehabilitation therapy. The sensory organisation test and dizziness handicap inventory were used to compare the pre- and post-training results of both rehabilitative treatments.Results: All group one patients in the standardised testing subset demonstrated improved results for both the composite sensory organisation test and for the functional transfer aspect of the dizziness handicap inventory, after five days' training with the electrotactile vestibular substitution system. In contrast, group two patients showed no significant improvement in their composite sensory organisation test or dizziness handicap inventory scores after eight weeks of therapy, compared with pre-treatment levels.Conclusion: These preliminary results indicate the efficacy of the electrotactile vestibular substitution system in improving patients' symptoms of vestibulopathy, and constitute evidence of successful sensory substitution. © 2010 JLO (1984) Limited.
Keywords: Inner Ear; Vertigo; Vestibular Rehabilitation